2023
DOI: 10.1038/s41420-023-01517-8
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and the bidirectional regulatory factor p53

Abstract: Ferroptosis is a type of regulated cell death characterized by iron-mediated lipid peroxidation, in contrast with apoptosis, autophagy, and necrosis. It can be triggered by many pathological processes, including cellular metabolism, tumors, neurodegenerative diseases, cardiovascular diseases, and ischemia–reperfusion injuries. In recent years, ferroptosis has been discovered to be associated with p53. P53 is a tumor suppressor protein with multiple and powerful functions in cell cycle arrest, senescence, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…In our study, we found that the P53 pathway was significantly increased in naive T cells of Trappc1 cKO mice. It is known that P53 could upreg-ulate the iron oxide reductase Steap3, which deoxidizes iron in Fe 3+ form to Fe 2+ [43]. Ultimately, DMT1-mediated release of Fe 2+ from endosomes into the cytoplasm leads to increased ROS production and increased lipid peroxidation [31,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that the P53 pathway was significantly increased in naive T cells of Trappc1 cKO mice. It is known that P53 could upreg-ulate the iron oxide reductase Steap3, which deoxidizes iron in Fe 3+ form to Fe 2+ [43]. Ultimately, DMT1-mediated release of Fe 2+ from endosomes into the cytoplasm leads to increased ROS production and increased lipid peroxidation [31,42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, P53 upregulates the iron oxide reductase Steap3, which reduces Fe 3+ form iron to Fe 2+ form iron. Ultimately, DMT1-mediated release of Fe 2+ from endosomes into the cytoplasm leads to increased ROS production and increased lipid peroxidation [31,43]. Thus, P53 is closely involved in the ferroptosis process.…”
Section: Trappc1 Suppresses Ferroptosis By Inhibiting the P53 Pathwaymentioning
confidence: 99%
“…The first category of ferroptosis inducers triggers this process by depleting GSH; the second category directly targets GPX4 inactivation to induce ferroptosis; the third category induces ferroptosis by impairing both GPX4 and CoQ10 through the SQSme-mevalonate pathway, while the fourth category promotes lipid peroxidation by increasing LIP (Labile iron pool) or iron oxide. 38,41,42 Therefore, iron, lipids, and ROS constitute the fundamental components underlying ferroptosis. 60,61 Iron is necessary for lipid peroxide accumulation and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ALOXs are non-heme iron-containing dioxygenases that catalyse the peroxidation and esterification of PUFAs, producing various biologically active lipid intermediates, including MDA. 49,65,68,69 P53 plays a crucial role in ferroptosis, 42,70,71 induces SAT1 expression, promoting ALOX15 function to enhance cell ferroptosis. 72,73 Wei Gu et al demonstrated that p53-ALOX12 can promote GSH-independent ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation